(untitled) (Journal of Pharma Insights and Research, 2025)
Hemophilia A and B are X-linked congenital bleeding disorders characterized by functional deficiencies in coagulation factor VIII (FVIII) and factor IX (FIX) that disrupt the intrinsic "tenase" complex, leading to impaired thrombin generation and defective fibrin clot formation. Although management has advanced from plasma-derived proteins to recombinant and extended half-life products, the formation of neutralizing alloantibodies (inhibitors) remains a major complication, precipitating therapeutic failure. The molecular pathology of the F8 and F9 genes, particularly structural variants like Intron 22 inversions, dictates clinical severity and predisposes patients to inhibitor development. Recent therapeutic paradigms have shifted towards non-factor replacement strategies, such as the bispecific antibody emicizumab, which restores hemostasis but complicates laboratory monitoring by altering the standard coagulation assays. Moreover, adeno-associated virus (AAV)-mediated gene transfer represents a transformative approach, offering sustained endogenous factor expression. The current knowledge of molecular genetics, inhibitor mechanisms, and these emerging biotechnological interventions is essential for optimizing clinical outcomes in the modern era of hemophilia care